Disclosure of non-current tangible assets information in local government financial statements: The case of Lithuania - Rasa Kanapickiene; Greta Keliuotyte-Staniuleniene (Economies, 2019)
The aim of the research is to examine and evaluate the accounting information disclosure quality of the non-current tangible assets in the financial statements of the municipalities of Lithuania and identify municipality characteristics having an impact on the accounting information disclosure quality. Although the question of Lithuania public sector accounting information disclosure quality has been relevant since the Public Sector Accounting and Financial Reporting Reform in 2010, this research is the first of its kind in Lithuania. Based on the legal and regulatory requirements and related scientific literature, the research model of the accounting information disclosure quality in the financial statements has been created. Using the content analysis of consolidated annual financial statements of Lithuanian municipalities (years 2013-2016), the disclosure quality index has been calculated, as well as the accounting information disclosure quality of the tangible assets has been evaluated and compared. The results show that the quality of accounting information disclosure of Lithuanian municipalities in 2013 was low (revealed 37.87% of the mandatory information), while in subsequent years, the disclosure of mandatory information increased (to 45.50% in 2016) and the quality of information disclosure became average. Multiple panel regression analysis revealed that specific factors such as size of the municipality, municipality debt-paying capacity, municipality tangible assets, and municipality revenue, have a statistically significant impact on the accounting information disclosure quality.
Keywords: H83; M41; M48; 330; accounting information disclosure quality; disclosure quality index; financial reporting; municipality; non-current tangible assets